If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 5 + -1q Solving 1 = 5 + -1q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add 'q' to each side of the equation. 1 + q = 5 + -1q + q Combine like terms: -1q + q = 0 1 + q = 5 + 0 1 + q = 5 Add '-1' to each side of the equation. 1 + -1 + q = 5 + -1 Combine like terms: 1 + -1 = 0 0 + q = 5 + -1 q = 5 + -1 Combine like terms: 5 + -1 = 4 q = 4 Simplifying q = 4
| 9y+4=-239 | | 0=9n-n | | 1/6x10-23g | | 4006=5k+6 | | 2h-2=12 | | (9.5x-75)/(X-15) | | 5=(10)-3+b | | 9y=36655413 | | 10=7a+3a | | 75=10u-5 | | 6x+4=2(x-5) | | 7/7(3)= | | 12=2+10 | | 6(7x+3)=42x | | -6-5x=8+2x | | 15=6k-3k | | Log(4+10)=0 | | 6y-5(y-2)+1=8 | | 3b+5=134 | | 9=5e-2e | | (e+1)*2=12 | | 3x-x/8=28 | | 4*12+15= | | 2(3X+14)-9=4X-21 | | 10=3x-x | | -60-13=83 | | 2(3x+6)+7=6x+19 | | 3x+4whenx=2 | | -2w^2+18=7x | | 2.5/35=2/b | | 20=2e+2e | | 2+-2=0 |